Innovative Psychotherapieforschung: auf dem Weg zu einer evidenz- und prozessbasierten individualisierten und modularen Psychotherapie - Brakemeier, Eva-Lotta; Herpertz, Sabine (Der Nervenarzt, 2019)
Psychotherapy has been proven to be effective; however, this statement applies in particular to the “average patient” in randomized controlled trials. As a considerable proportion of patients do not show any benefits despite the constant development of new therapy methods and the mechanisms of action are still too little understood, innovative psychotherapy research has to address both problems. In addition, the idea of personalization that originated in somatic medicine or - from our point of view more appropriately - individualization or person-centering should be taken up. After providing an overview of further developments in psychotherapy beyond disorder-specific methods, this article presents an evidence- and process-based individualized and modular psychotherapy as a visionary goal of psychotherapeutic research: Beyond syndromes and disorders, as many biopsychosocial characteristics as possible and the processes and mechanisms underlying the mental problems should be analyzed and bundled in an individual comprehensive functional analysis. Based on this functional analysis, evidence-based techniques and modules should be selected. The individual response during the course of therapy should be continuously documented, so that feedback helps to determine the further therapeutic procedure. In order to pursue this vision, studies are needed that are oriented towards the individual patient, investigate the central mechanisms of action and generate large translational datasets. These should be analyzed by ideographic analyses and reduce the gap between research and practice, thus contributing to the paradigm of a practice research network, which is now consistently moving to the centre of research.
Gesehen am 16.01.2020